2020
DOI: 10.3390/pathogens9121073
|View full text |Cite
|
Sign up to set email alerts
|

Animal and Human Vaccines against West Nile Virus

Abstract: West Nile virus (WNV) is a widely distributed enveloped flavivirus transmitted by mosquitoes, which main hosts are birds. The virus sporadically infects equids and humans with serious economic and health consequences, as infected individuals can develop a severe neuroinvasive disease that can even lead to death. Nowadays, no WNV-specific therapy is available and vaccines are only licensed for use in horses but not for humans. While several methodologies for WNV vaccine development have been successfully applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 41 publications
(48 reference statements)
1
22
0
Order By: Relevance
“…No specific drug or therapy is currently licensed to treat WNV infections [27,28]. While there is no approved vaccine for humans to date [29,30], three vaccines are approved in Europe for the vaccination of horses. The licensed vaccines contain a West Nile recombinant canarypox virus [31], a chimeric yellow fever-West Nile vector [32], or inactivated West Nile virus [33], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…No specific drug or therapy is currently licensed to treat WNV infections [27,28]. While there is no approved vaccine for humans to date [29,30], three vaccines are approved in Europe for the vaccination of horses. The licensed vaccines contain a West Nile recombinant canarypox virus [31], a chimeric yellow fever-West Nile vector [32], or inactivated West Nile virus [33], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of infections in humans are asymptomatic while the rest may develop mild or severe disease of neuroinvasive nature and potentially death 6 . There are currently no licensed vaccines nor antiviral treatments for humans 3 , 7 , but four licensed vaccines are on the market for use in equines 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a study carried out in Southern Italy concluded that vaccines used do not alter the overall hemogram picture and health status of horses though it is associated with modulation of humoral immunity, leukocyte populations, and inflammatory markers [ 24 ]. Contrariwise, to date, no vaccine is available for human [ 25 , 26 , 27 , 28 ]: Even though several vaccines targeting flaviviruses (e.g., TBE, yellow fever, Dengue, Japanese encephalitis, and Kyasanur forest disease) have been made available, none has been licensed for the use against WNV infection [ 29 , 30 , 31 ]. Moreover, none of the vaccine candidates has progressed further than to phase I/II clinical trial [ 32 ].…”
Section: Introductionmentioning
confidence: 99%